Tindak Pidana Pemerkosaan dalam Perspektif Perlindungan Hukum Perempuan - Teo Dentha Maha Pratama; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2020)
A criminal act refers to an act that is prohibited by legal regulations accompanied by threats in the form of sanctions such as the application of certain crimes. The criminal act of rape in the Criminal Code is included in the category of decency. Criminal acts of rape can be referenced from the Book II of the Criminal Code. In this regard, this study focuses on two issues: (1) legal protection of women victims of rape from a women’s legal perspective and (2) criminal sanctions against perpetrators of the criminal acts of rape against women. This study makes use of the normative method because there is an empty norm. Legal protection for women as victims of rape correlatable in Article 285 of the Criminal Code Paragraph (1) and Paragraph (2) as well as the Domestic Violence Law (KDRT) Number 23 of 2004 Article 46 concerning Sexual Violence in the household. This regulation only regulates the sanctions for perpetrators of the acts of rape against women. Sanctions for perpetrators of the rape against women are regulated in Article 285 Paragraph (1) and Paragraph (2) which can also be seen in Law Number 23 of 2004 Article 46 concerning the Elimination of Domestic Violence with imprisonment or the same fine.